Replacement analysis using probabilistic life cycle costing - Mulubrhan, F. (Asian Research Publishing Network, 2016)
Life-cycle cost (LCC) is the most frequently used economic model for decision making that considers all costs in the life of a system or equipment. The LCC of repairable equipment highly depends on the reliability and availability of the equipment. Optimum equipment reliability reduces failure which in turn reduces disruption of product that have a direct link to maintenance and production cost. This paper presents a mathematical model to estimate the life cycle cost (LCC) of repairable equipment. Operation and Maintenance cost are calculated using activity based costing. Pump system containing two pumps in a parallel configuration is taken as a case and their LCC is analyzed using the developed model. The developed model is used to assess alternative replacement option of the existing pump system. The alternative options are either to continue with the existing system or to replace one of the pumps that have highest downtime or to replace both pumps. Â© 2006-2016 Asian Research Publishing Network (ARPN).